The Effect of Work-Life Balance and Rewards on Performance Mediated by Psychological Well-Being - Pebriyanti, Ni wayan Peri; Subiyanto, Didik; Prayekti, Prayekti; Lada, Suddin (Universitas Mercu Buana, 2025)
Objective: This study aims to determine the influence of Work-Life Balance and Reward in improving Work Performance with Psychogical Well-Being as a mediating variable.Methods: The study was conducted at Stanagiri Luxury and Khastana in the areas of Tegal Suci, Sebatu, Tegallalang, Gianyar, Bali with 120 samples using purposive sampling. The data was processed using SPSS to describe the demographics of the respondents, and AMOS SEM to confirm the hypothesis.Results: Work-Life Balance had a significant and positive effect on Psychological Well-Being. Work Life Balance has a significant and positive effect on work performance. Reword has no effect on Psychological Well-being. Rewards have no effect on Work Performance. Psychological Well-Being has a significant and positive effect on Work Performance. Psychological Well-Being mediates the relationship between Work-Life Balance and Individual Work Performance. Psychological Well-Being mediates the relationship between Reward and Job Performance.Conclusion: Work-Life Balance has a positive and significant effect on Psychological Well-being and Work Performance. On the other hand, Rewards do not have a significant effect on Psychological Well-Being or Work Performance. Psychological well-being has a positive and significant effect on Work Performance and acts as a mediator in the relationship between Work-Life Balance, Reward, and Individual Work Performance.